Matrix Metalloproteinase-2 Mediates Intestinal Immunopathogenesis in Campylobacter Jejuni-Infected Infant Mice - Alutis, Marie E. (Eur J Microbiol Immunol (Bp), 2015)
Increased levels of the matrix metalloproteinases (MMPs)-2 and -9 (also referred to gelatinase-A and -B, respectively) can be detected in the inflamed gut. We have recently shown that synthetic gelatinase blockage reduces colonic apoptosis and pro-inflammatory immune responses following murine Campylobacter (C.) jejuni infection. In order to dissect whether MMP-2 and/or MMP-9 is involved in mediating C. jejuni-induced immune responses, infant MMP-2(–/–), MMP-9(–/–), and wildtype (WT) mice were perorally infected with the C. jejuni strain B2 immediately after weaning. Whereas, at day 2 postinfection (p.i.), fecal C. jejuni B2 loads were comparable in mice of either genotype, mice expelled the pathogen from the intestinal tract until day 4 p.i. Six days p.i., colonic MMP-2 but not MMP-9 mRNA was upregulated in WT mice. Remarkably, infected MMP-2(–/–) mice exhibited less frequent abundance of blood in feces, less distinct colonic histopathology and apoptosis, lower numbers of effector as well as innate and adaptive immune cells within the colonic mucosa, and higher colonic IL-22 mRNA levels as compared to infected WT mice. In conclusion, these results point towards an important role of MMP-2 in mediating C. jejuni-induced intestinal immunopathogenesis.